Inhaled corticosteroids and adverse outcomes among chronic obstructive pulmonary disease patients with community-acquired pneumonia: a population-based cohort study - Basille, Damien; Wang, Lei; Thomsen, Reimar Wernich; Menon, Jyothi; Shetty, Nisha; Duhaut, Pierre; Andrejak, Claire; Jounieaux, Vincent; Sørensen, Henrik Toft (Frontiers in Medicine, 2023)
Introduction While inhaled corticosteroids (ICS) may increase pneumonia risk in patients with chronic obstructive pulmonary disease (COPD), the impact of ICS on pneumonia outcomes is debated. We examined whether ICS use is associated with adverse outcomes among COPD patients with community-acquired pneumonia (CAP). Materials and methods Population-based cohort study of all COPD patients with an incident hospitalization for CAP between 1997 and 2013 in Northern Denmark. Information on medications, COPD severity, comorbidities, complications, and death was obtained from medical databases. Adjusted risk ratios (aRRs) for pleuropulmonary complications, intensive care unit (ICU) admissions, and 30-day mortality in current and former ICS users were compared with those in non-users, using regression analyzes to handle confounding. Results Of 11,368 COPD patients with CAP, 6,073 (53.4%) were current ICS users and 1,733 (15.2%) were former users. Current users had a non-significantly decreased risk of pleuropulmonary complications [2.6%; aRR = 0.82 (0.59–1.12)] compared to non-users (3.2%). This was also observed among former users [2.5%; aRR = 0.77 (0.53–1.12)]. Similarly, decreased risks of ICU admission were observed among current users [aRR = 0.77 (0.57–1.04)] and among former users [aRR = 0.81 (0.58–1.13)]. Current ICS users had significantly decreased 30-day mortality [9.1%; aRR = 0.72 (0.62–0.85)] compared to non-users (12.6%), with a stronger association observed among patients with frequent exacerbations [0.58 (0.39–0.86)]. No significant association was observed among former ICS users [0.89 (0.75–1.05)]. Conclusion Our results suggest a decreased risk of death with ICS use among COPD patients admitted for CAP.